A diagnostic test for cocaine and benzoylecgonine in urine and oral fluid using portable mass spectrometry. Issue 12 (21st November 2016) - Ismail, Mahado; Baumert, Mark; Stevenson, Derek; Watts, John; Webb, Roger; Costa, Catia; Robinson, Fiona; Bailey, Melanie
Abstract : Surface mass spectrometry methods can be difficult to use effectively with low cost, portable mass spectrometers. Abstract : Surface mass spectrometry methods can be difficult to use effectively with low cost, portable mass spectrometers. This is because commercially available portable (single quadrupole) mass spectrometers lack the mass resolution to confidently differentiate between analyte and background signals. Additionally, current surface analysis methods provide no facility for chromatographic separation and therefore are vulnerable to ion suppression. Here we present a new analytical method where analytes are extracted from a sample using a solvent flushed across the surface under high pressure, separated using a chromatography column and then analysed using a portable mass spectrometer. The use of chromatography reduces ion suppression effects and this, used in combination with in-source fragmentation, increases selectivity, thereby allowing high sensitivity to be achieved with a portable and affordable quadrupole mass spectrometer. We demonstrate the efficacy of the method for the quantitative detection of cocaine and benzoylecgonine in urine and oral fluid. The method gives relative standard deviations below 15% (with one exception), and R 2 values above 0.998. The limits of detection for these analytes in oral fluid and urine are <30 ng ml −1, which are comparable to the cut-offs currently used in drug testing, making the technique a possible candidate for roadside or clinic-based drug testing.